Poverty, inequality, and development - Fields, Gary S. (Cambridge [Eng.] ; New York : Cambridge University Press, 1980)
Economists have traditionally concentrated on aggregate economic growth to measure a country's development, but previously they have also considered income distribution performance. In this book Gary Fields reverses conventional approaches by using income distribution as the primary indicator. He examines what is known about the distribution of income and poverty, inequality, and development. He explores the main causes of poverty and inequality and the extent to which they have been reduced by individual countries in the course of their economic growth. Recognizing that conclusions vary with the type of income distribution measure used, Fields proposes that changes in absolute poverty be adopted as the primary index of a developing nation's progress and suggests that the growth rate of the GNP and character of that growth be regarded as the principal determinants of the levels of poverty and inequality. This framework calls for new models new data. and new microanalytic techniques in order to understand the results of development efforts. Fields employs evidence from case studies of six developing nations to suggest some explanations for differing patterns of development and calls for development planning founded on a firm commitment to helping the poor.
Includes index.
Bibliography: p. [258]-272.
oo 24/01/2019
Loans
Keywords: Economic development; Income distribution; Equality